1980
DOI: 10.1128/aac.18.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antibacterial activities of diarylamidine derivatives

Abstract: The antifungal and antibacterial properties of a series of 70 diarylamidine derivatives were evaluated. Several of these compounds exhibited considerable antimicrobial potency. A survey of the structure-activity relationship demonstrated that minor structural variations resulted in significant changes of antimicrobial activity. In general, the structural features required for antifungal activity coincided with those required for antibacterial activity. Both the antifungal and the antibacterial properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…This class of compounds has been evaluated previously for antimicrobial properties (2), as well as for antiproteolytic, anticoagulant (23), and antiproliferative activity (5). In our study, four bis-(imidazolinylindole) compounds from the diarylamidine library exhibited very potent activity in the macrophage rescue screen.…”
Section: Taken Together These Results Indicate That the Bis-(imidazomentioning
confidence: 75%
“…This class of compounds has been evaluated previously for antimicrobial properties (2), as well as for antiproteolytic, anticoagulant (23), and antiproliferative activity (5). In our study, four bis-(imidazolinylindole) compounds from the diarylamidine library exhibited very potent activity in the macrophage rescue screen.…”
Section: Taken Together These Results Indicate That the Bis-(imidazomentioning
confidence: 75%
“…the determinant bind to a variety of anionic compounds including nucleic acids, mast-cell heparin and mucopolysaccharides. Bis(guany1hydrazones) (Denny and Cain, 1979), quaternary ammonium compounds (Scott, 1962) and diamidine compounds such as propamidine and amicarbalide (Anne et al, 1980) bind to nucleic acids, and the DNA-intercalating properties of ethidium bromide (Cain et al, 1978) and the acridines (Wolfe et al, 1972) have been well documented. This common property of binding to nucleic acids has prompted us to refer to the determinant encoding resistance to these compounds as the NAB (nucleic acid-binding compounds)-resistance determinant.…”
Section: Discussionmentioning
confidence: 99%
“…16 Because the length of these target molecules varies significantly it was necessary to compare the DNA binding of these molecules to oligomers of varying AT-tracts. Table 16.9 contains comparisons of DT m values for furamidine (17) and its three extended analogs 29-31 with three different oligomers with 4,6-and 8-AT base pair binding sites. Subsequently, 29 has been found to bind to DNA in an unusual dimer motif which has potential for development of a new gene-regulation paradigm [144][145][146].…”
Section: Dicationic Furans 439mentioning
confidence: 99%
“…However, on oral administration of pentamidine dioxime in the immunosuppressed rat model for PCP it was only moderately effective [106]. We have reported that the bisamidoxime and bis-O-methylamidoxime of furamidine (17) were quite effective anti-PCP agents in the rat model on both oral and intravenous administration (see Tab. 16.13) [108]. However, the bis-O-ethylamidoxime of 17 was ineffective, demonstrating a remarkable sensitivity to structure.…”
Section: Pro-drug Approaches For Furamidinementioning
confidence: 99%